Length of Stay dengan Kepuasan Keluarga Pasien Prioritas dapat dipengaruhi oleh Peran Perawat sebagai Care Giver: Length of Stay with Priority Patient Family Satisfaction can be influenced by the Nurse's Role as Care Giver - Mat Yani (Dohara POAJ, 2021)
Introduction: The role of nurses as caregivers which were given during the emergency unit will continue to interact between nurses and patients. There are twelve reports of dissatisfaction with outpatient services. Complementary data in hospitalized there are nine reports of dissatisfaction with inpatient services. So that the relationship and interaction between nurse and patient will greatly determine the level of patient satisfaction. Methods: This study used a descriptive analytic method using a correlation research study with cross sectional approach. The population in this study were priority patients in emergency unit is based on the average monthly patient rate in 2019, which were 915 priority patients in the emergency room. The sampling technique in this study was using the purposive sampling method, used 90 respondents. Results: The role of the nurse as a care giver and the length of stay with the priority patient's family satisfaction had a significant relationship (P value 0.024). Discussion: The satisfaction was felt by patients as indicated by nurses who have find patient expectations for excellent and high-quality services in terms of information accuracy, timely service, and nurses' readiness to find problems in order to help them.